2018
DOI: 10.3389/fendo.2018.00449
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Association of Circulating SIRT1 and Adiposity: A Study on Underweight, Normal Weight, and Obese Patients

Abstract: Context: Sirtuins (SIRTs) are NAD+-dependent deacetylases, cellular sensors to detect energy availability, and modulate metabolic processes. SIRT1, the most studied family member, influences a number of tissues including adipose tissue. Expression and activity of SIRT1 reduce with weight gain and increase in conditions of starvation.Objective: To focus on SIRT1 plasma concentrations in different conditions of adiposity and to correlate SIRT1 with fat content and distribution, energy homeostasis and inflammatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 39 publications
6
37
0
Order By: Relevance
“…To our knowledge, there is no evidence that sirtuin activity in blood represents sirtuins leaking out of solid organs (skeletal and cardiac muscle). It has previously been shown that sirtuin levels in blood correlate with different organ dysfunctions like coronary heart disease in obese patients [8][9][10]62] or type 1 and type 2 diabetes [11]. Exercise leads to metabolic stress in different organs and it would not ethically be sound to take biopsies from multiple organs in humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, there is no evidence that sirtuin activity in blood represents sirtuins leaking out of solid organs (skeletal and cardiac muscle). It has previously been shown that sirtuin levels in blood correlate with different organ dysfunctions like coronary heart disease in obese patients [8][9][10]62] or type 1 and type 2 diabetes [11]. Exercise leads to metabolic stress in different organs and it would not ethically be sound to take biopsies from multiple organs in humans.…”
Section: Discussionmentioning
confidence: 99%
“…The acetylation level of the mitochondrial proteome is 65% [7] which makes these proteins amenable to regulation by sirtuins. Blood levels of sirtuins were shown to correlate with several organ dysfunctions like coronary heart disease in obese patients [8][9][10] or type 1 and type 2 diabetes [11].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to being linked to physical activity, SIRT1 is implicated in the development of addictions 11,12 , anxiety 13,14 , and depression [14][15][16][17] , all of which are elements of AN, reinforcing the notion that this enzyme might play a key role in the pathology of AN. Furthermore, two recent studies showed an upregulation of SIRT1 expression in AN models of rodents 18,19 , while another found an increase in SIRT1 protein levels in humans with AN 20 , all of which further suggest a link between AN and SIRT1.…”
mentioning
confidence: 87%
“…The SIRT1 levels were determined according to the manufacturer's instructions using quantitative ELISAs (MyBioSource, Cod. GDMBS705558) as previously described [13]. Adiponectin was measured by Human Total Adiponectin/Acrp30 Quantikine ELISA kit (DRP300, R&D Systems, Minneapolis, MN, USA).…”
Section: Plasma Sirt1 Adiponectin and Leptin Assaymentioning
confidence: 99%
“…SIRT1 modulates gluconeogenesis in the liver, pancreatic ß cell insulin secretion [10], adipocyte differentiation [11] and heart protection [12]. In the case of overnutrition, tissue and plasma levels of SIRT1 are reduced, predisposing to metabolic derangement and its sequelae [13,14]. Indeed, SIRT1 inversely correlates with FM, and its reduction is associated with liver steatosis and increased epicardial fat thickness (EFT) in obese patients [15][16][17].…”
Section: Introductionmentioning
confidence: 99%